PROJECT TO IMPROVE SERVICE, PRODUCTION AND DISTRIBUTION OF A DINING BAR USING THE ARENA SIMULATION SOFTWARE - Augusti, Natália Carolina; Embalde, Isabela Lourenço Panosso; Mendes, Oswaldo Lazaro (Revista Interface Tecnológica, 2022)
This work aims to improve the services of a cafeteria, optimizing customer service and response time to orders. As a basis for this project, bibliographic research was used based on books, internet articles and on-site visits for data collection. The work used the Design Thinking methodology and through the ARENA simulator, it proposed an improvement in the service system, production and distribution of the cafeteria orders, so that they will have higher quality and shorter response time to orders. As a result, the simulation showed a considerable bottleneck in the preparation of snacks and another much smaller bottleneck in delivery via motorcycle from the cafeteria and a new scenario presented as a solution showed a considerable reduction in the queue for preparing snacks. It is concluded that simulation tools such as ARENA are essential to help managers to solve bottleneck problems in companies.
Keywords: Process improvement; Simulation; ARENA Software